CRO Cloud Survey-based clinical information systems and methods of use - KANG, SAN (2023)
An embodiment of the present invention provides a cloud survey type CRO system and a control method, wherein the system comprises: a gateway server that performs mapping, filtering, routing, authentication, and load balancing of all users' HTTP service requests; a cloud CRO management device composed of a service management server that comprehensively manages the registration and status management of all servers in the system to respond to users' service requests; a cloud API server that makes communications with the cloud CRO management device through the HTTP protocol and creates and controls an independent CRO API server for each drug for clinical use; and a CRO API server that is created as a virtual server for each drug to be subject to a clinical test by the cloud API server, enables a survey-type case report form (S-CRF) to be freely edited and formed for each drug without the requirement of program coding, makes communications with the cloud CRO management device through the HTTP communications, processes users' clinical-related service requests routed by the cloud CRO management device, and stores clinical investigation result data in a database independent for each drug. Costs for purchasing security equipment for each drug can be remarkably reduced. 본 발명의 일 실시 예에 따른 클라우드 설문방식CRO시스템 및 제어방법은, 모든 사용자의 HTTP서비스 요청을 매핑(Mapping), 필터링(filtering), 라우팅(Routing), 보안(Authentication), 로드밸런싱(Load balancing)을 하는 게이트웨이서버와, 사용자의 서비스 요청에 대응하기 위한 시스템 내의 모든 서버의 등록(Registration)과 상태관리(Health Check)를 통합적으로 관리하는 서비스관리서버로 구성된 클라우드CRO관리장치; 상기 클라우드CRO관리장치와 HTTP프로토콜로 통신을 하며, 임상을 위한 약품마다 독립적인 CRO API서버를 생성하고 관제하는 클라우드 API서버; 상기 클라우드API서버에 의해 임상시험 대상이 될 약품별 가상서버로 생성되고, 프로그램 코딩 필요없이 설문방식 증례기록서(S-CRF)를 약품별로 자유롭게 편집하여 구성할 수 있으며, 상기 클라우드CRO관리장치와 HTTP통신을 하며, 클라우드CRO관리장치에 의해 라우팅 된 사용자의 임상과 관련한 서비스 요청을 처리하고, 임상조사 결과 데이터를 약품별로 독립된 데이터베이스에 저장하는 CRO API서버를 포함한다.